PENERAPAN TEKNOLOGI IRIGASI BERBASIS TENAGA SURYA UNTUK MENINGKATKAN PRODUKTIVITAS PERTANIAN DI DUSUN PUTAT, KAPANEWON PATUK, GUNUNGKIDUL - Santoso, Gatot; Hani, Slamet; Rusianto, Toto; Wahid, Rindo Maulana; Sidik, Khalil; Wijaya, Dwi Anggra (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
The aim of this activity is to improve the welfare of farmers in Padukuhan Gumawang, Putat Village, Gunungkidul, through the application of irrigation technology that uses renewable energy, namely solar power. The majority of the population in this village are farmers who depend heavily on agricultural products, especially rice and secondary crops. However, one of the main problems faced is limited water during the dry season, which causes a decrease in agricultural productivity. Therefore, innovative and sustainable solutions are needed to overcome this problem. The method used in community service is designing and testing a tool to obtain a Solar Power Plant (PLTS) as an energy source to operate a submersible pump to support a more efficient and energy-saving irrigation system. Activities carried out include outreach to farmers regarding the benefits of renewable energy technology, PLTS design and installation, as well as equipment maintenance training. Apart from that, ongoing assistance is also provided so that farmers can independently manage this system. The results of this activity show an increase in farmers' understanding of the use of environmentally friendly technology and renewable energy. The PLTS-based irrigation system has succeeded in increasing agricultural land productivity by up to 30% and significantly reducing operational costs, especially savings in terms of purchasing fuel. Apart from that, the application of this technology also contributes to reducing carbon emissions in the region. Thus, this program is able to double the productivity of secondary crops, provide direct financial benefits to farmers and provide a positive and sustainable impact on improving the welfare of farmers in Padukuhan Gumawang.